2019
DOI: 10.1111/bjd.17867
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double‐blind trial comparing 5‐aminolaevulinic acid nanoemulsion with methyl 5‐aminolaevulinate in daylight photodynamic therapy for actinic keratosis

Abstract: Linked Article: Räsänen et al. Br J Dermatol 2019; https://doi.org/10.1111/bjd.17311

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
1
0
Order By: Relevance
“…However, 7 days after the first PDT procedure, the intensity of pain was significantly lower in the areas treated with MAL-HCl or ALA-P (1.4 and 1.3 on average, respectively) than in the areas treated with ALA-HCl (1.8 on average). In most of the studies, patients reported more acute pain at the site of ALA-HCl application [20,[34][35][36][37][38][39]. However, in the reports by Yazdanyar et al, who compared the pain response to ALA-HCl and MAL treatment of the scalp and forehead AK lesions, no significant differences in pain intensity between these two formulations were found either during or 30 min after the completion of treatment [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, 7 days after the first PDT procedure, the intensity of pain was significantly lower in the areas treated with MAL-HCl or ALA-P (1.4 and 1.3 on average, respectively) than in the areas treated with ALA-HCl (1.8 on average). In most of the studies, patients reported more acute pain at the site of ALA-HCl application [20,[34][35][36][37][38][39]. However, in the reports by Yazdanyar et al, who compared the pain response to ALA-HCl and MAL treatment of the scalp and forehead AK lesions, no significant differences in pain intensity between these two formulations were found either during or 30 min after the completion of treatment [40].…”
Section: Discussionmentioning
confidence: 99%